Value of hospital resources for effective pressure injury prevention: a cost-effectiveness analysis - Padula, William V; Pronovost, Peter J; Makic, Mary Beth F; Wald, Heidi L; Moran, Dane; Mishra, Manish K; Meltzer, David O (BMJ quality & safety, 2019)
ObjectiveHospital-acquired pressure injuries are localised skin injuries that cause significant mortality and are costly. Nursing best practices prevent pressure injuries, including time-consuming, complex tasks that lack payment incentives. The Braden Scale is an evidence-based stratification tool nurses use daily to assess pressure-injury risk. Our objective was to analyse the cost-utility of performing repeated risk-assessment for pressure-injury prevention in all patients or high-risk groups.DesignCost-utility analysis using Markov modelling from US societal and healthcare sector perspectives within a 1-year time horizon.SettingPatient-level longitudinal data on 34 787 encounters from an academic hospital electronic health record (EHR) between 2011 and 2014, including daily Braden scores. Supervised machine learning simulated age-adjusted transition probabilities between risk levels and pressure injuries.ParticipantsHospitalised adults with Braden scores classified into five risk levels: very high risk (6–9), high risk (10–11), moderate risk (12–14), at-risk (15–18), minimal risk (19–23).InterventionsStandard care, repeated risk assessment in all risk levels or only repeated risk assessment in high-risk strata based on machine-learning simulations.Main outcome measuresCosts (2016 $US) of pressure-injury treatment and prevention, and quality-adjusted life years (QALYs) related to pressure injuries were weighted by transition probabilities to calculate the incremental cost-effectiveness ratio (ICER) at $100 000/QALY willingness-to-pay. Univariate and probabilistic sensitivity analyses tested model uncertainty.ResultsSimulating prevention for all patients yielded greater QALYs at higher cost from societal and healthcare sector perspectives, equating to ICERs of $2000/QALY and $2142/QALY, respectively. Risk-stratified follow-up in patients with Braden scores <15 dominated standard care. Prevention for all patients was cost-effective in >99% of probabilistic simulations.ConclusionOur analysis using EHR data maintains that pressure-injury prevention for all inpatients is cost-effective. Hospitals should invest in nursing compliance with international prevention guidelines.